Expression of cell cycle proteins in head and neck cancer correlates with tumor site rather than tobacco use - Haas, Susanne; Hörmann, Karl; Bosch, Franz X. (Oral oncology, 2002)
Head and neck squamous cell carcinomas of non-smoking patients may result from specific defects in cell cycle control. Expression of p53, pRb, p16INK4a and Cyclin D1 was examined by immunohistochemistry of biopsies obtained from 24 non-smoking and 25 smoking patients, both groups representing similar clinical features (tumor site, stage of disease, gender). Expression of p16INK4a was restricted to carcinomas of the tonsils (8/24), P=0.0069. In 6/8 p16INK4a-positive cases, expression of pRb was absent or reduced. p16 was the only marker showing a significant correlation with a negative smoking history (P=0.0208). Overexpression of Cyclin D1 was frequent in carcinomas of the tongue (6/14) but rare in tonsillar carcinomas (2/24), P=0.0303. Expression of p53 was independent of the smoking history and the tumor site. Our results implicate that there are factors other than tobacco consumption which may influence the development of head and neck cancers at distinct tumor sites.